Sistem Distribusi Obat Dan Alat Kesehatan Pada PT. Parit Padang Global - Thalita Novi Salsabilla (CV. ITTC INDONESIA, 2022)
Hospitals or drug stores that have pharmaceutical installations that receive supplies of drugs and medical devices from PT. Parit Padang Global can evaluate suppliers of drugs and medical devices.mThrough SalesmenmKnow the products and goods to be sold well and serve consumers with requests for prescription and non-prescription drugs. CSSAmmThis process begins with a customer need. namely TO DO (delivery order) data in the warehouse section that is sent to the warehouse admin for printing. After CCSA sends the data, the warehouse admin will issue a letter that has been received and printed it for the collection of drugs and medical devices ordered by consumers. Handover of Coordinator I Where the collection of goods is in accordance with what was taken by RF (radio frequency), Coordinator I will re-check the goods that have been taken by warehouse employees by checking the paper or DO (delivery order) letter. Coordinator II Conducts re-checks to avoid errors. Expedition (shipping service)